Analisis Kesediaan Membayar (Willingness to Pay) Beras Merah Organik oleh Konsumen di Kota Surakarta - Hollanda Bronovita Ulfa; Ernoiz Antriyandarti; Agustono Agustono (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
Organic red rice is a food source that contains antioxidants. This rice has an outer layer of bran which is a good source of protein, fiber, fat, and vitamin E. This research aims to analyze the willingness to pay for organic red rice and the factors that influence it. The basic method used is descriptive analysis. The research location is Surakarta City which is chosen using purposive method. The research respondents amounted to 100 people using accidental sampling. The Contingent Valuation Method (CVM) method is used to determine the average value of maximum WTP, and multiple linear regression analysis to determine the factors that influence consumer WTP. The average value of willingness to pay for organic red rice in Surakarta City is IDR. 33,264,- per kilogram. Age, income, trust, scarcity, health awareness and environmental awareness have a positive effect on the WTP value. Other factors such as number of family members, attributes, conspicuous consumption, and gender have no effect on the WTP value. The factor that most influences the willingness to pay for organic red rice in Surakarta City is trust.